2022
DOI: 10.1021/acs.analchem.2c01869
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Energy-Resolved Mass Spectrometry Distributions from Surface-Induced Dissociation

Abstract: Understanding the relationship between protein structure and experimental data is crucial for utilizing experiments to solve biochemical problems and optimizing the use of sparse experimental data for structural interpretation. Tandem mass spectrometry (MS/MS) can be used with a variety of methods to collect structural data for proteins. One example is surface-induced dissociation (SID), which is used to break apart protein complexes (via a surface collision) into intact subcomplexes and can be performed at mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…RosettaDock has had many successes in modeling quaternary protein structure 58 . And its docking predictive capabilities can be further enhanced with the inclusion of sparse experimental data [59][60][61][62] . The benefit of using integrative modeling is that the results depend on the combination of Rosetta score and experimental data correlation, not one individually.…”
Section: Structure Prediction With Covalent Labeling Datamentioning
confidence: 99%
“…RosettaDock has had many successes in modeling quaternary protein structure 58 . And its docking predictive capabilities can be further enhanced with the inclusion of sparse experimental data [59][60][61][62] . The benefit of using integrative modeling is that the results depend on the combination of Rosetta score and experimental data correlation, not one individually.…”
Section: Structure Prediction With Covalent Labeling Datamentioning
confidence: 99%
“…Previous work demonstrated that incorporating sparse data from techniques such as structural mass spectrometry and nuclear magnetic resonance into conventional physics/knowledge-based algorithms, such as Rosetta, led to more accurate predictions. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] When combined with deep learning, sparse data can be used to develop models which outperform AlphaFold2, such as using experimental contacts from photocrosslinking mass spectrometry 27,28 or density maps from cryo-electron microscopy 29 .…”
Section: Introductionmentioning
confidence: 99%